1992
DOI: 10.1021/bi00146a021
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the sterol- and actin-binding domains of plasma vitamin D binding protein (Gc-globulin)

Abstract: The mammalian plasma vitamin D binding protein (DBP), or Gc-globulin, is recognized to have at least two functional properties: sterol binding and G-actin sequestration. Affinity labeling of the sterol binding site with the radioactive electrophilic ligand, 3 beta-(bromoacetoxy)-25-hydroxycholecalciferol, followed by limited proteolysis, permitted the isolation and identification of three overlapping peptides in the amino terminus of the molecule. When G-actin affinity chromatography was applied to other prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(47 citation statements)
references
References 52 publications
4
41
0
1
Order By: Relevance
“…In agreement with a study that used limited proteolysis to identify the sterol-binding site (35), Verboven et al localize this site to the N terminus of DBP (34). Such a location is distal to the actin-binding interface identified in this work, which provides a structural understanding of previous reports that the sterol-binding and actin-binding properties of DBP are independent (35)(36)(37)(38). It also seems reasonable to propose that the large structural differences between DBP and HSA are directed toward its actin-binding function, which involves specific interactions with all three domains of DBP and not toward its sterol-binding property, which is confined to the first four ␣-helices of DBP.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…In agreement with a study that used limited proteolysis to identify the sterol-binding site (35), Verboven et al localize this site to the N terminus of DBP (34). Such a location is distal to the actin-binding interface identified in this work, which provides a structural understanding of previous reports that the sterol-binding and actin-binding properties of DBP are independent (35)(36)(37)(38). It also seems reasonable to propose that the large structural differences between DBP and HSA are directed toward its actin-binding function, which involves specific interactions with all three domains of DBP and not toward its sterol-binding property, which is confined to the first four ␣-helices of DBP.…”
Section: Resultssupporting
confidence: 91%
“…The structure of DBP complexed with a vitamin D metabolite has been reported very recently (34). In agreement with a study that used limited proteolysis to identify the sterol-binding site (35), Verboven et al localize this site to the N terminus of DBP (34). Such a location is distal to the actin-binding interface identified in this work, which provides a structural understanding of previous reports that the sterol-binding and actin-binding properties of DBP are independent (35)(36)(37)(38).…”
Section: Resultssupporting
confidence: 80%
“…Distinct binding regions within the 458 amino acid sequence of DBP have been identified. Analysis of the crystal structure of DBP (bound to either vitamin D 3 or actin) has confirmed previous studies that the vitamin D sterol binding segment resides in the N-terminal domain (amino acids 35-49) (Haddad et al, 1992;Swamy et al, 1997), and also revealed that actin interacts with distinct amino acid sequences in all three DBP domains Otterbein et al, 2002;Swamy et al, 2002;Verboven et al, 2002). Recently, our lab has identified a C5a chemotactic cofactor region in the N-terminal domain (amino acids 130-149), a sequence distinct from either the vitamin D or G-actin binding regions (Zhang and Kew, 2004).…”
Section: Introductionsupporting
confidence: 78%
“…A 1.8-kb SalI-XhoI fragment containing the PGK-promoter/neomycin phosphotransferase (PGK-neo r ) cassette was blunt-end ligated into exon 5 of the mDBP fragment at the BamHI site to generate pDBPN5. To shorten the construct, pDBPN5 was digested with SalI and KpnI by removing a 2.3-kb fragment containing exons 2 and 3 generating pDBPN5 (4)(5)(6)(7)(8). The diphtheria toxin A chain gene (DTA) cassette (17) (generous gift from Barbara Knowles, The Jackson Laboratory, Bar Harbor, Maine, USA) on a 2.7-kb SalI-KpnI fragment was ligated to the KpnI-SalI pDBPN5(4-8) fragment, and circularized recombinants were selected.…”
Section: Methodsmentioning
confidence: 99%